Measures for mitigating the delay in high-rise building construction projects in Dubai - Bhatti, Imtiaz Ali (2019)
Construction industry faces several challenges such as low labour productivity, cost overrun, time overrun, and extreme weather condition. Globally, the most severe challenge is project delay, particularly in Dubai where the construction industry is booming rapidly than other parts of the world, especially in high-rise building construction projects. Hence, objectives of this research are to identify the factors causing delay, to determine the significant factors and their mitigation measures, and to assess relationship between significant factors of delay and their mitigation measures. This study consists of two stages. In stage one, based on 56 common factors causing delay in construction projects identified from literature review, a questionnaire survey was designed and distributed to 100 respondents among the construction practitioners. Through SPSS version (20) analysis, 11 out of 56 common factors were found to be significant factors causing delay. In stage two, a preliminary study was initially carried out by developing a semi-structured questionnaire which was distributed among 30 construction experts in order to determine the mitigation measures for each of 11 significant delay factors. The 44 mitigation measures associated respectively with each of the 11 significant factors were then utilized in the development of final questionnaire. This finalized questionnaire was distributed among 100 construction experts of high-rise building construction projects in order to assess the relationship between significant factors and their mitigation measures. It was unveiled from bivariate analysis of Pearson correlation coefficient that relationship between significant factors and their mitigation measures has very significant, positive and linearly correlated with each other. This research would be helpful for all construction practitioners who are involved in high-rise building construction projects in mitigating the relative delay to the project. Thus, it will directly benefit the construction community and contribute in raising the economy of the country.